Characterization of Ag/AgCl Dry Electrodes for Wearable Electrophysiological Sensing - Lee, Min Suk; Paul, Akshay; Xu, Yuchen; Hairston, W. David; Cauwenberghs, Gert (Frontiers in Electronics, 2022)
With the rising need of on-body biometric sensing, the development of wearable electrophysiological sensors has been faster than ever. Surface electrodes placed on the skin need to be robust in order to measure biopotentials from the body reliably, and comfortable for extended wearability. The electrical stability of non-polarizable silver/silver chloride (Ag/AgCl) and its low-cost, commercial production, has made these electrodes ubiquitous health sensors in the clinical environment, where wet-gels and long wires are accommodated by patient immobility. However, smaller, dry electrodes with wireless acquisition are essential for truly wearable, continuous health sensing. Currently, techniques for the robust fabrication of custom Ag/AgCl electrodes are lacking. Here, we present three methods for the fabrication Ag/AgCl electrodes: oxidation of Ag in a chlorine solution, electroplating Ag, and curing Ag/AgCl ink. Each of these methods are then used to create 3 different electrode shapes suitable for wearable application. Bench-top and on-body evaluation of the electrode techniques was achieved by electrochemical impedance spectroscopy (EIS), calculation of variance in electrocardiogram (ECG) measurements and analysis of Auditory Steady-State Response (ASSR) measurement. Microstructures produced on the electrode by each fabrication technique were also investigated with scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX). The custom Ag/AgCl electrodes were found to be performant in comparison to standard, commercial Ag/AgCl wet electrodes across all 3 of our presented techniques, with Ag/AgCl ink shown to be the better out of the three in bench top and biometric recordings.